2017
DOI: 10.1080/10872981.2017.1386042
|View full text |Cite
|
Sign up to set email alerts
|

Identification of core objectives for teaching sustainable healthcare education

Abstract: Background: Physicians will be called upon to care for patients who bear the burden of disease from the impact of climate change and ecologically irresponsible practices which harm ecosystems and contribute to climate change. However, physicians must recognize the connection between the climate, ecosystems, sustainability, and health and their responsibility and capacity in changing the status quo. Sustainable healthcare education (SHE), defined as education about the impact of climate change and ecosystem alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 25 publications
1
68
0
Order By: Relevance
“…This is similar to the finding from the survey of NMA physicians that "a majority of respondents said that physicians have a responsibility to bring the health effects of climate change to the attention of their patients (75%) and the public (71%)" [17]. The similarities in these findings suggest that there is a need to include education on pollution, climate change and health in health professional education, both at Yale and nationally [23]. This education should train health professionals to understand the complex ways in which climate change and pollution impact health [31], how to effectively communicate these health impacts to patients, and how to conserve resources and prevent pollution in clinical practice.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is similar to the finding from the survey of NMA physicians that "a majority of respondents said that physicians have a responsibility to bring the health effects of climate change to the attention of their patients (75%) and the public (71%)" [17]. The similarities in these findings suggest that there is a need to include education on pollution, climate change and health in health professional education, both at Yale and nationally [23]. This education should train health professionals to understand the complex ways in which climate change and pollution impact health [31], how to effectively communicate these health impacts to patients, and how to conserve resources and prevent pollution in clinical practice.…”
Section: Discussionsupporting
confidence: 78%
“…Previous research has examined physician knowledge and attitudes about climate change and health, medical waste, and duty to educate patients [17][18][19][20][21][22]. Physicians have identified a need for improved health professional education to prepare them to respond to climate change related harm and to better communicate with patients, the public, and policy makers [17,23,24]. A recent study found that medical students in China understood the health impacts of climate change but did not feel adequately prepared to address these impacts [25].…”
Section: Health Professional Understanding Of Climate Change Pollutimentioning
confidence: 99%
See 1 more Smart Citation
“…• Education for health care professionals on environmental sustainability should include o general knowledge about the climate crisis effects on population health, including 10,11 ▪ air pollution, ▪ exposure to toxins, ▪ heat-related illnesses, 10,11 ▪ extreme weather events, 10,11 ▪ physical and mental health effects of natural disasters, 12 ▪ need for reliable access to clean food and water, and ▪ modification of vector-borne, zoonotic, and waterborne diseases 13 ; o disaster preparedness 10 ; o health system infrastructure resilience [14][15][16][17] ; o supply chain engagement 18 ; o financial, social, and environmental benefits of environmental best practices 19 ; and o real-world examples of environmental best practices in health care services. • Environmentally responsible decision-making in health care delivery should align with local, state and federal regulations and support patient safety and optimal clinical outcomes.…”
Section: Position Statementmentioning
confidence: 99%
“…For example, in the United Kingdom, the General Medical Council consulted widely in the development of sustainability learning objectives, 7 which have been identified in a recent best‐evidence medical education guide 8 as providing an appropriate framework for health professions' education. An international collaboration developed learning outcomes and activities for an environmentally accountable curriculum, and a recent Delphi study has also developed learning outcomes 9 , 10 . Despite this, there are few examples in the literature where climate change and health has been integrated into medical curricula.…”
mentioning
confidence: 99%